DRUGS USED IN HEART FAILURE (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
Heart failure is the  most commoncardiovascular reason for hospital admission for people older than 60years of age.Few areasin medicine have progressed as remarkably as heart failure treatment over the past three decades. However, progress has been consistent only for chronic heart failure with reducedejection fraction, none of the treatments tested to dars have been definitively proven to improve survival.Delaying or preventing heart failure has become increasingly important in patients who are prone to heart failure.The prevention of worsening chronic heart failure and hospitalisations for acute decompensation is also of great importance.